2013
DOI: 10.1111/jne.12062
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Control of Reproductive Behaviour by Locally Synthesised Oestrogens: Focus on Aromatase

Abstract: Oestrogens activate nucleus-and membrane-initiated signalling. Nucleus-initiated events control a wide array of physiological and behavioural responses. These effects generally take place within relatively long periods of time (several hours to days). By contrast, membrane-initiated signalling affects a multitude of cellular functions in a much shorter timeframe (seconds to minutes). However, much less is known about their functional significance. Furthermore, the origin of the oestrogens able to trigger these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…The precise mechanism through which T is acting cannot be determined in the present study, but recent research has identified intriguing rapid effects of steroid hormones achieved by non-genomic mechanisms (Cornil et al, 2013;Mangiamele and Thompson, 2012), including effects on acoustic communication (RemageHealey and Bass, 2010;Remage-Healey and Joshi, 2012). Aromatase conversion of the precursor T to estradiol has been identified as a key process in rapid modulation of vocal behavior (Schlinger et al, 1999), which is interesting considering that aromatase expression in the medial preoptic area (mPOA), a nucleus with known involvement in both sexual and parental behavior (Dominguez and Hull, 2005;Kentner et al, 2010), increases in response to fatherhood in male California mice (Trainor et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The precise mechanism through which T is acting cannot be determined in the present study, but recent research has identified intriguing rapid effects of steroid hormones achieved by non-genomic mechanisms (Cornil et al, 2013;Mangiamele and Thompson, 2012), including effects on acoustic communication (RemageHealey and Bass, 2010;Remage-Healey and Joshi, 2012). Aromatase conversion of the precursor T to estradiol has been identified as a key process in rapid modulation of vocal behavior (Schlinger et al, 1999), which is interesting considering that aromatase expression in the medial preoptic area (mPOA), a nucleus with known involvement in both sexual and parental behavior (Dominguez and Hull, 2005;Kentner et al, 2010), increases in response to fatherhood in male California mice (Trainor et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…While it is true that no estrogen is produced in the absence of aromatase, changes in enzyme activity can result in increases or decreases in tissue estrogen levels with no change in aromatase expression. In fact, such changes have been shown to occur relatively quickly and appear to account for at least some behaviors related to estrogen in the brain of animals (Cornil et al, 2013, Dickens et al, 2014). To gain a complete picture of normal and abnormal changes in regional estrogen synthesis capacity, it would be advantageous to develop radiotracers which are substrates rather than non-competitive inhibitors of the enzyme.…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
“…Brain-derived steroids provide a local source of neuromodulators that can act upon neural circuits at rapid timescales akin to classical neurotransmitters (seconds to minutes) [2]. While the rapid effects of steroid hormones are often studied in the context of sexual behavior [3], the role of neurosteroids in behaviors and neural systems beyond reproduction has only recently received attention. One area in particular has been understanding how estrogen signaling may enhance or otherwise alter cognition on momentary timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is important to clarify the functional role of reduced neural E2 production in the acquisition of sensory experience, in songbirds, rats and other model systems. In particular, key future research directions include understanding the acute control mechanisms for in vivo brain aromatase activity (such as calcium-dependent phosphorylation of the enzyme [3]), as well as improving our temporal resolution for the fluctuations in neuroestradiol during and following discrete learning events.…”
Section: Introductionmentioning
confidence: 99%